Increased B-lymphopoiesis by interleukin 7 induces bone loss in mice with intact ovarian function: Similarity to estrogen deficiency - Miyaura, Chisato (The National Academy of Sciences of the USA, 1997)
Estrogen deficiency caused by ovariectomy (OVX) results in a marked bone loss due to stimulated bone resorption by osteoclasts. During our investigations of the pathogenesis of bone loss in estrogen deficiency, we found that OVX selectively stimulates B-lymphopoiesis which results in marked accumulation of B220-positive pre-B cells in mouse bone marrow. To examine the possible correlation between stimulated B-lymphopoiesis and bone loss, 8-week-old female mice were treated with interleukin (IL) 7, which stimulates B-lymphopoiesis in bone marrow. We also examined bone mass in IL-7 receptor-knockout mice that exhibit marked suppression of B-lymphopoiesis in the bone marrow. The increased B-lymphopoiesis induced by IL-7 administration resulted in marked bone loss by stimulation of osteoclastic bone resorption in mice with intact ovarian function. The changes in both B-lymphopoiesis and bone mass in IL-7-treated female mice were similar to those in age-matched OVX mice. In contrast, the trabecular bone volume of the femur was greatly increased in both female and male IL-7 receptor-knockout mice when compared with the respective wild-type and heterozygous littermates. These results show that the perturbation of B-lymphopoiesis in the bone marrow is closely linked to the change in bone mass. We propose here that the increased B-lymphopoiesis due to estrogen deficiency is involved in the mechanism of stimulated bone resorption.